Comparison of the molecular interactions of 7′-carboxyalkyl apigenin derivatives with S. cerevisiae α-glucosidase. (April 2017) - Qi, Y.J.; Lu, H.N.; Liang, J.X.; Zhao, Y.M.; Wang, X.E.; Jin, N.Z.
Graphical abstract: Highlights: With the increasing of length of the alkyl chain in carboxyalkyl group, B ring of the apigenin derivatives is embedded much more deeply into the binding cavity while carboxyalkyl stretches to the neighboring cavity. The electron density values of the carbonyl in the carboxyl group become higher than the solution status due to the strong molecular interactions. All of the HOMO and LUMO are distributed throughout the whole apigenin ring in solution phase, whereas the disappeared phenomenon happened on the B rings of some molecules (II–VI), leading to higher energy gaps. Abstract: As one of the most investigated flavonoids, apigenin, is considered to be a strong α-glucosidase inhibitor. However, the clinical utility of apigenin is limited due to its low solubility. It was reported that the solubility and biological activity can be improved by introducing sole carboxyalkyl group into apigenin, especially the 7′-substitution. With the increase of length of the alkyl chain in carboxyalkyl group, B ring of the apigenin derivative is embedded much more deeply into the binding cavity while the carboxyalkyl stretches to the neighboring cavity. All of the terminal carboxyl groups form hydrogen bonding interactions easily with the surrounding polar amino acids, such as His239, Ser244, Arg312 and Asp349. Thus, the electron density values of the carbonyl in the carboxyl group become higher than the solution status due to the strong molecular interactions. In fact, electron densities of most of the chemical bonds are decreased after molecular docking procedure. On compared with the solution phase, however, dipole moments of most of these molecules are increased, and their vectors are reoriented distinctly in the active sites. It is noticed that all of the Highest Occupied Molecular Orbital (HOMO) and Lowest Unoccupied Molecular Orbital (LUMO) are distributed throughout the whole parent apigenin ring in solution phase, whereas the disappeared situation happened on the B rings of some molecules (II–IV) in the active site, leading to higher energy gaps.